Pendekatan-Pendekatan dan Strategi Pendidikan Pencegahan Salahgunaan Dadah - Ismail, Maznah; Choo, Choo; P.F. & Hoo, P.F. & Hoo (Penerbit Universiti Sains Malaysia, 1986)
This paper attempts to provide an overview of several major approaches and strategies used in the drug prevention programmes. It attempts to explain the basic rationale of drug abuse prevention programmes and to discuss three major approaches, viz, knowledge/attitude approach, value approach and psycho-social competency approach. In addition, the discussion will also dwell on some of the strategies used in each of these approaches.